EVALUATION AND SELECTION OF SEED NUMBER IN THE FRUIT OF CAPPARIS SPINOSA L BASED ON PRODUCTIVITY INDICATORS - Ш. М. Эргашев (Web of Journals Publishing, 2024)
Of particular importance is the scientific basis for the germination of seeds of the plant Capparis spinosa L.
Keywords: Areas, fruits, seeds, fertility, productivity.